FAKTOR PENGHINDARAN PAJAK: ANALISIS TERHADAP FINANCIAL DISTRESS, SALES GROWTH, DAN PERAN KOMISARIS INDEPENDEN : TAX AVOIDANCE FACTORS: ANALYSIS OF FINANCIAL DISTRESS, SALES GROWTH, AND THE ROLE OF INDEPENDENT COMMISSIONERS - Yulianti, Nur Wachidah; Pratiwi, Adelia (Universitas Riau, 2024)
This research aims to examine the influence of financial distress, sales growth, environmental uncertainty and independent commissioners on tax avoidance. The population in this research are manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange during the 2019-2023 period. This research uses the purposive sampling method. Based on the specified sample criteria, a total of 110 samples were obtained that could be processed. This research is quantitative research and the data analysis method used is multiple linear regression analysis. The results of this research show that financial distress and sales growth had a positive effect on tax avoidance. Meanwhile, environmental uncertainty did not affect tax avoidance and independent commissioners had a negative effect on tax avoidance. This research has a contribution for the government in formulating tax policies.